The Behavioral Responses of the Chiguanco Thrush to Urbanization in a Neotropical City Comes From Preadapted Behavioral Traits - Garitano-Zavala, Álvaro; Calbimonte, Rodrigo; Esteve-Herraiz, Guillermo (Frontiers in Ecology and Evolution, 2022)
Several animal species can survive within cities by changing their behavior; such changes could be the result of evolutionary adaptation, epigenetic effects, or come from preadapted traits through phenotypic plasticity or non-random dispersal. Exploring whether behavioral preadapted traits are present in non-urbanized populations could improve our understanding of the processes that allow animals to cope with urbanization. We compared the boldness, neophobia, and solving-test skills of adult individuals of the Chiguanco Thrush (Turdus chiguanco) between urban and extra-urban habitats in La Paz, a high-altitude Neotropical city. The urban Chiguanco Thrushes were bolder, less neophobic, and performed better in problem-solving tests. Extra-urban individuals varied significantly more among them in boldness and neophobia, and although a smaller proportion of individuals were able to solve the simplest problem-solving test, they did so in the same way as the urban ones. This evidence suggests that the behavioral responses of the Chiguanco Thrush to urbanization in La Paz come from preadapted traits.